Quality of Financial Reporting of the Enterprise: Evaluation Methodology - Pravdiuk, Nataliia; Bondarenko, Valerii; Pokynchereda, Vitalii; Timchenko, Olga (European Journal of Sustainable Development, 2021)
The article substantiates the necessity of carrying out the assessment of the quality of financial reporting of the enterprise with the purpose of inserting the level of its information filling to the needs of users and increasing their confidence in the institute of accounting. Proceeding from it theoretical and methodological positions of estimation of quality of the financial reporting on the basis of use of the theory of qualimetry are developed. The proposed model covers three consecutive stages, which provide for the description of the process of assessing the quality of financial reporting, the formation of a system of indicators for assessing the quality of financial reporting and determining the scale of their assessment, the quantitative assessment of qualitative properties of financial reporting, the analysis of the results of assessing the quality of financial reporting and management decisions. It is grounded that practical application of the developed method of assessment of financial reporting quality in contrast to the existing methods allows the development of separate models of assessment of financial reporting quality taking into account the needs of specific groups of users of accounting information and in accordance with the priority of qualitative properties of financial reporting defined by them.